Penerapan CPPB-IRT pada Kelompok Pengasapan Ikan Dengan Bahan Bakar Kayu yang Berbeda di Desa Langgam, Pelalawan, Riau - Sukmiwati, Mery; Leksono, Tjipto; Fionasari, Dwi (Unri Conference Series: Community Engagement, 2024)
Fish smoking in Langgam Village is done traditionally and has been passed down from generation to generation. The use of different wood fuels provides different quality smoking results. The fuels that are often used are laban wood, coconut shells and corn cobs. There are several smoked fish processing groups that use different wood fuels that have commercial potential in Langgam village. The types of fish that are usually processed are selais, baung and catfish.The problem based on the survey results faced by the fishery product processing group in this village is that the smoked fish processing group does not yet have knowledge about CPPB-IRT. The aim of this service activity is to find solutions to every problem raised by the group, so that smoked fish products can compete in the market and expand marketing reach outside the province. The method used in this service is qualitative by collecting data through interviews, observation, counseling, training and mentoring of smoked fish processing groups. The results of the activity show that group members have gained knowledge and understanding about CPPB-IRT for processing smoked fish and know the best fuel to use for processing smoked fish.